Anisotropic mosaicity and lattice-plane twisting of an m-plane GaN homoepitaxial layer. Issue 27 (14th June 2019) - Kim, Jaemyung; Seo, Okkyun; Tanaka, Atsushi; Chen, Jun; Watanabe, Kenji; Katsuya, Yoshio; Nabatame, Toshihide; Irokawa, Yoshihiro; Koide, Yasuo; Sakata, Osami
Abstract : We have observed anisotropic mosaicity of an m -plane GaN homoepitaxial layer by X-ray diffraction topography imaging over a wafer and X-ray rocking curves measured at various wafer points. Abstract : We have observed anisotropic mosaicity of an m -plane GaN homoepitaxial layer by X-ray diffraction topography imaging over a wafer and X-ray rocking curves measured at various wafer points. Crystal domains were well aligned along the [0001] directions, but showed higher mosaicity along the [1̄21̄0] direction. Images reconstructed from the full-width at half maximum showed stripe patterns along the [0001] direction. From the bending-angle images at two different azimuthal angles, we found that GaN (101̄0) planes were twisted along the [1̄21̄0] direction, which generated anisotropic features. High resolution X-ray rocking curves revealed the multi-domain structure of GaN (101̄0) along the [1̄21̄0] direction. The evaluated bending-angle distribution of 0.030 ± 0.013° mainly originated from the epitaxial layer twisting. We propose two possible mechanisms for this anisotropic feature and the stripe patterns correlated with epitaxial layer twisting.